Effects of fish oil supplement on psoriasis: a meta-analysis of randomized controlled trials - Shih-Jyun Yang; Ching-Chi Chi (BMC, 2019)
Abstract Background Fish oils, which contain omega-3 polyunsaturated fatty acids as the active ingredients, possess anti-inflammatory activities and may have therapeutic potential in diseases with an inflammatory etiology. Fish oil supplement has been advocated for treating psoriasis which is a chronic inflammatory dermatosis. Objective We aimed to investigate the effects of fish oil supplement on psoriasis. Methods We searched CENTRAL, Embase and MEDLINE on 24 January 2018 for randomized control trials (RCTs) on the effects of fish oil supplement in treating psoriasis. The Cochrane Collaboration's tool was used to assess the risk of bias of included RCTs. We performed a random-effects model meta-analysis to obtain the pooled treatment effect estimates. Results We included 13 RCTs with 625 participants. Three RCTs involving 337 participants provided usable data for meta-analysis. Fish oil supplement did not significantly reduce the severity of psoriasis when assessed by Psoriasis Area and Severity Index score (mean difference − 0.28; 95% confidence interval − 1.74 to 1.19). Conclusion The current evidence does not support the use of fish oil supplement in treating psoriasis.